Impact of apoptotic adipose-derived mesenchymal stem cells on attenuating organ damage and reducing mortality in Rat sepsis syndrome induced by cecal puncture and ligation - Chang Chia-Lo; Leu Steve; Sung Hsin-Ching; Zhen Yen-Yi; Cho Chung-Lung; Chen Angela; Tsai Tzu-Hsien; Chung Sheng-Ying; Chai Han-Tan; Sun Cheuk-Kwan; Yen Chia-Hung; Yip Hon-Kan (Journal of Translational Medicine, 2012)
Abstract Background We tested whether apoptotic adipose-derived mesenchymal stem cells (A-ADMSCs) were superior to healthy (H)-ADMSCs at attenuating organ damage and mortality in sepsis syndrome following cecal ligation and puncture (CLP). Methods Adult male rats were categorized into group 1 (sham control), group 2 (CLP), group 3 [CLP + H-ADMSC administered 0.5, 6, and 18 h after CLP], group 4 [CLP + A-ADMSC administered as per group 3]. Results Circulating peak TNF-α level, at 6 h, was highest in groups 2 and 3, and higher in group 4 than group 1 (p < 0.0001). Immune reactivity (indicated by circulating and splenic helper-, cytoxic-, and regulatory-T cells) at 24 and 72 h exhibited the same pattern as TNF-α amongst the groups (all p < 0.0001). The mononuclear-cell early and late apoptosis level and organ damage parameters of liver (AST, ALT), kidney (creatinine) and lung (arterial oxygen saturation) also displayed a similar pattern to TNF-α levels (all p < 0.001). Protein levels of inflammatory (TNF-α, MMP-9, NF-κB, ICAM-1), oxidative (oxidized protein) and apoptotic (Bax, caspase-3, PARP) biomarkers were higher in groups 2 and 3 than group 1, whereas anti-apoptotic (Bcl-2) biomarker was lower in groups 2 and 3 than in group 1 but anti-oxidant (GR, GPx, HO-1, NQO-1) showed an opposite way of Bcl-2; these patterns were reversed for group 4 (all p < 0.001). Mortality was highest in group 3 and higher in group 2 than group 4 than group 1 (all p < 0.001). Conclusions A-ADMSC therapy protected major organs from damage and improved prognosis in rats with sepsis syndrome.